The fading productivity of schooling in East Asia - Erich Gundlach; Ludger Wößmann (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
We compare changes in schooling output and in schooling input of six East Asian countries to derive a measure of productivity change. Our results question the impression that all is well with education in East Asia. First, we find that the cognitive achievement of pupils did not change substantially in 1980-94 (except for the Philippines, where it most likely declined). Hence schooling output largely remained flat or worsened. Second, we find that the relative price of schooling increased by more than would be warranted by zero productivity growth in schooling. Therefore, we conclude that schooling productivity has declined. The main reason for the fading productivity of schooling appears to be a decline in the pupil-teacher ratio.
Keywords: I2; 330; Bildungsinvestition; Schule; Bildungsniveau; Produktivität; Schätzung; Theorie; Ostasien; Hongkong; Japan; Philippinen; Singapur; Südkorea; Thailand